Antimicrobial activity against some human pathogenic microorganisms of silk spiders; Agelena labyrinthica (Agelenidae) and Holochnemus pluchei (Pholcidae) - Bayda Hameed; Derya İşler Ceyhan; Adile Akpınar (Journal of Natural Fibers, 2025)
Nowadays, where the use of biological materials is increasing, the antimicrobial activities of ethanol, methanol, and acetone extracts of silk from the species Agelena labyrinthica (Clerck, 1757) (Agelenidae) and the acetone extract of silk from the species Holocnemus pluchei (Scopoli, 1763) (Pholcidae), which produces insufficient silk, have been studied. Extracts from both spider species were tested against three Gram-negative bacteria (Pseudomonas aeruginosa (ATCC 27,853), Klebsiella pneumonia (ATCC 700,603), and Escherichia coli (ATCC 25,922)), one Gram-positive bacteria (Staphylococcus aureus (ATCC 25,923)), and one yeast (Candida albicans (ATCC 90,028)). It was determined that the inhibition zone diameters created by H. pluchei silk acetone extract against E. coli, P. aeruginosa, and K. pneumonia during 24-h incubation period (14 ± 0.1 mm, 11 ± 0.2 mm, 6.5 ± 0.5 mm, respectively) were greater than those created by A. labyrinthica acetone extract (12 ± 0.2 mm, 7 ± 0.0 mm, 6 ± 0.1 mm, respectively). However, it was found that H. pluchei silk acetone, A. labyrinthica ethanol, and methanol extracts had no antimicrobial activity against S. aureus, but A. labyrinthica silk acetone extract created an inhibition zone diameter of 9.5 ± 0.5 mm. Accordingly, it was determined that the antimicrobial activities of spider silks varied depending on the spider species and the solvent used to obtain the silk extract.